2008
DOI: 10.1080/09585170802357470
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes approaches to assessment: comparing non‐government and government case‐study schools in Western Australia

Abstract: A key feature of recent curriculum reform in post‐industrialised liberal economies has been the ascendancy of outcomes‐based education policies. A 1995 review conducted in Western Australia (WA) recommended an outcomes‐based approach, and in response, the Curriculum Framework (CF) was released in 1998. The same year, the WA State government mandated that all schools, both non‐government and government, demonstrate compliance with the outcomes‐based CF for Years K–10 by 2004. This article compares case‐studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The impact of such coverage on teachers has rarely been directly examined. While a limited number of studies (Blackmore and Thorpe, 2003; Hargreaves et al, 2007; Liu and Tsao, 2013) have sought teacher responses to news coverage, most of what is known about teachers’ reactions to news has emerged from research that has considered other issues such as teacher retention (Fetherston and Lummis, 2012) and policy change (Griffiths et al, 2008). In Australia, teachers have reported that news coverage regarding schools and teaching can affect their relationships with friends, family and the wider community (Blackmore and Thorpe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of such coverage on teachers has rarely been directly examined. While a limited number of studies (Blackmore and Thorpe, 2003; Hargreaves et al, 2007; Liu and Tsao, 2013) have sought teacher responses to news coverage, most of what is known about teachers’ reactions to news has emerged from research that has considered other issues such as teacher retention (Fetherston and Lummis, 2012) and policy change (Griffiths et al, 2008). In Australia, teachers have reported that news coverage regarding schools and teaching can affect their relationships with friends, family and the wider community (Blackmore and Thorpe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to Bentley (2010), change due to purposes of access refers to expanding education opportunities in countries. Arguably, this has links to global education agendas advocated by the World Bank (Coxon & Tolley, 2005;Griffiths, Vidovich & Chapman, 2008). For instance, the "Education For All" (EFA) movement signed by 165 countries in Jomtien, Thailand in 1990, and re-asserted in Dakar, Senegal in 2000, is an example of an access change that has influenced educational changes globally (Nongas, 2007).…”
Section: Reasons For Innovationmentioning
confidence: 99%
“…This finding asserts there is a need to change teachers' pedagogical knowledge from a teacher-centred approach to a student-centred that the policy required (Sections 4.3.3 and 7.1.1.2). Indeed, it is noted that teachers need the theoretical and practical PD knowledge of the OBE concept (Griffiths et al, 2008). Because if there is no support such as PD for teachers, then, as aptly described by Hall and Kidman (2004), "you can't change knowledge if you don't have knowledge" (p. 341).…”
Section: Professional Development Needmentioning
confidence: 99%
See 1 more Smart Citation